Repensando orientação para o mercado no Brasil - Faria, Alexandre de A. (2009)
As one of the outcomes of the process of dissemination of the free market capitalism model, the concept of market orientation has become one of the most important in the field of marketing as of the 1990s. The first studies in market orientation were undertaken in the US and focused only large business firms. Subsequently, in parallel to the expansion of the free market capitalism model, research started to be undertaken in developing countries and emerging economies. Finally, research embraced also public organizations and non-profit organizations. These studies helped raise the strategic status of the field of marketing but also to detach researchers from criticisms about the relevance of the discipline and from important developments made by other fields about market, academy and emerging economies. This article argues that the concept of market orientation reproduces assumptions that are inadequate to the understanding and representation of the market in emerging economies - as Brazil - in the age of globalization. At the end, the article presents the guidelines of an interdisciplinary framework to the project of rethinking marketing orientation in Brazil.